Taxonomic studies on Palaearctic and Oriental Eudorylini (Diptera: Pipunculidae), with the description of three new species - Kehlmaier, Christian (Zootaxa, 2005)
Taxonomic evidence of 17 species of Eudorylini occurring in the extra-European part of the Palaearctic and/or in the Oriental Region is presented. Among the material, three new taxa are described as new to science: Claraeola perpaucisquamosa Kehlmaier spec. nov. from China, Dasydorylas gradus Kehlmaier spec. nov. from Israel and Eudorylas bipertitus Kehlmaier spec. nov. from Israel. Lectotypes for Pipunculus nitidifrons Becker, 1900 and Pipunculus oppletus Collin, 1941 are designated. Two new synonymies are proposed [syn. nov.]: Pipunculus confusoides Lamb, 1922 as junior synonym of P. nitidifrons Becker, 1900 and Claraeola koreana Skevington, 2001 as junior synonym of P. oppletus Collin, 1941. Furthermore, the following new generic combinations are introduced (partly redescribed and figured) [comb. nov.]: Claraeola colossus (Hardy, 1972), Claraeola conjuncta (Collin, 1949), Claraeola discors (Hardy, 1966), Claraeola koreana (Kozánek & Kwon, 1991), Claraeola oppleta (Collin, 1941), Claraeola palgongsana (Kozánek, Suh & Kwon, 2003), Claraeola robusta (Kozánek, Suh & Kwon, 2003), Clistoabdominalis nitidifrons (Becker, 1900), Clistoabdominalis sinaiensis (De Meyer, 1995), Clistoabdominalis subruralis (Kozánek & Kwon, 1991), Clistoabdominalis uniformis (Brunetti, 1917), Clistoabdominalis uzbekistanus (Kozánek, 1988). A replacement name had to be selected for Claraeola koreana Skevington, 2001: 435 [Preocc. Kozánek & Kwon, 1991a]: Claraeola paektusana Kehlmaier, 2005 nom. nov.. Also, the male of Eudorylas mongolorum Kuznetzov, 1990 is redescribed and its genitalia figured, as are the male genitalia of Claraeola adventitia (Kertész, 1912).